Neolithic cultivation of water chestnuts (Trapa L.) at Tianluoshan (7000-6300 cal BP), Zhejiang Province, China. Issue 1 (December 2017) - Guo, Yi; Wu, Rubi; Sun, Guoping; Zheng, Yunfei; Fuller, Benjamin
Abstract Water chestnuts (Trapa ) are frequently recovered at Neolithic sites along the Lower Yangtze River Valley and have been important components of the diets of prehistoric people. However, little systematic research has been conducted to determine their cultural and dietary importance. Excavations at the Tianluoshan site produced large quantities of well-preserved specimens, which provide an excellent collection for studying morphological changes with time. Using modern wild and domesticated water chestnuts (n = 447) as a reference, we find Neolithic samples (n = 481) at Tianluoshan are similar in shape but smaller in size compared to the domesticated speciesTrapa bispinosa . In particular, the Tianluoshan water chestnuts have bigger seeds than the wild speciesTrapa incisa . Further, water chestnuts diachronically increased in size at the Tianluoshan site with significant differences (one-way, ANOVA) observed for length (p = 7.85E-08), height (p = 3.19E-06), thickness (p = 1.2E-13), top diameter (p = 5.04E-08) and bottom diameter (p = 1.75E-05) between layers 7 (6700-6500 cal BP) and 6 (6500–6300 cal BP). These results suggest that water chestnuts were actively selected based on size (big), shape (full fruit, two round horns, wide base, etc.) and were an important non-cereal crop to the agricultural practices at the Tianluoshan site.